Sanggar Seni Tari Al-Manar Sebagai Ruang Alternatif Pendidikan Seni dalam Memperkuat Martabat Budaya (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Art studios exist as alternative educational spaces that enable the transmission of cultural values ​​in a contextual and sustainable manner. This study aims to examine the mechanisms of culture-based learning and analyze the process of forming cultural dignity at the Al-Manar Dance Studio in Medan City. The research uses a qualitative approach with a case study design. Data were collected through observation, interviews, and document studies. Then, the data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data presentation, and drawing conclusions. Research results show that the culture-based learning mechanism at Al-Manar Dance Studio takes place through three main stages: direct involvement in dance practice, symbolic interpretation of cultural values, and internalization through aesthetic experiences and social interactions. This process contributes to the formation of cultural dignity marked by growing cultural awareness, a sense of belonging, self-confidence, and pride in local culture. The study's findings emphasize that Al-Manar Dance Studio not only serves as an art training space but also as an alternative cultural education space that is effective in building the cultural identity of young people amid the flow of globalization.